Formação permanente de professores do ensino médio em uma escola da rede jesuíta de educação e os desdobramentos na prática pedagógica: uma viagem aos passos dados e caminhos futuros - Carvalho, Albanisa Gomes de Moura (Universidade do Vale do Rio dos Sinos, 2021)
This qualitative research aims to analyze the actions and relationships that express the assumptions of ongoing training in teaching pedagogical practice experienced in high school at a confessional school in Fortaleza-CE. Aiming this, I conducted a case study, based on the analysis of education documents from the Companhia de Jesus, literature review and application, for the production of data, a questionnaire and a comprehensive interview. The interlocutors and the context of the study involve five male and female teachers who work in high school, a pedagogical director and a pedagogical coordinator who work in the Jesuit Education Network school in the city of Fortaleza, the locus of the research. Thus, in order to achieve the general objective, I outlined the following specific objectives: to examine the assumptions of permanent teacher training present in the guiding documents of the Jesuit Education Network and Santo Inácio School - CE; to identify the assumptions of the permanent formation of teachers in the Political Pedagogical Project - PPP - of Santo Inácio School - CE; understand the perception of high school teachers regarding the type of training developed in the investigated school and analyze the consequences that such training has in the pedagogical practice of teachers. Those Objectives led me to find the categories: training perceived as updating, loss of teaching knowledge and training for practice. For the construction of the theoretical assumptions that support this study, I counted on the contributions of authors who discuss permanent formation, among them: Imbernón; Freire; Rosa; Arnhold; Lima; Nóvoa; Poglia, among others. The results present a characterization of training with assumptions of updating and technical rationality to comply with a demand for changes and innovations in a teaching performance perspective.
Keywords: Formação de professores do ensino médio; Formação de professores na Rede Jesuíta de Educação; Formação permanente de professores; Formação humanista; Formation of high school teachers; Teacher training in the Jesuit Education Network; Lasting teacher training; Humanist formation; ACCNPQ::Ciências Humanas::Educação